For geographical imagination systems. Issue 1 (2nd January 2021) - Bergmann, Luke; Lally, Nick
Abstract : For many, Geographic Information Systems (GIS) and related libraries for programming languages define the terrain of geographical computing today. But what if GIS were locales within wider realms of geographical imagination systems (gis), realms more adequate to diverse theoretical commitments of geographical thought? Examining how various thinkers in spatial theory have conceived of phenomena, space, knowledge, and their entanglements, this article advocates for geographical imagination systems that change the infrastructures of geographical computation and broaden its associated objects of intellectual inquiry. In doing so, it centers questions such as: What if knowledge were understood as interpreted experience? What if phenomena were represented as individuated out of process and internal relations? What if spaces and coordinates were coproduced with phenomena? Interludes juxtapose such considerations with concrete possibilities realized by an experimental prototype geographical imagination system under development. As the article also argues, though, crucial to the future of geographic computation adequate to geographical inquiry will be diverse creative conversations in code (valued alongside and) intellectually interwoven with scholarly interventions made through mediums such as the written word.